Seismic performance improvement of a slender composite ultra-high voltage bypass switch using assembled base isolation. (1st September 2019) - Xie, Qiang; Yang, Zhenyu; He, Chang; Xue, Songtao
Highlights: Test of an assembled isolation for slender composite equipment. An equivalent simplified model for optimal selection of dampers. Comparison between the wire rope isolation and the assembled isolation. Discussion on the influence of seismic inputs on the effectiveness of isolation. Abstract: Since the seismic performance of the bypass switch (BPS) cannot satisfy the stress safety factor requirement, an isolated combination of wire ropes with linear viscous dampers was employed. The assembled base isolation was designed using modal parameters, and the effectiveness of the isolation was validated numerically using finite element (FE) analysis and experimentally by the shaking table test. The numerical study shows that wire rope isolation can reduce the stress of a BPS considerably. Furthermore, the implementation of supplementary viscous dampers can further reduce the stress and, more importantly, displacement response, which is significant for UHV equipment. The middle section of BPS generates obvious high frequency vibration during test, although the root section still experiences the maximum stress response. Besides, testing verified the reliability of the FE model and confirmed that the stress safety factor requirement was satisfied. Therefore, the isolation comprised of wire ropes and a viscous damper is proposed to improve the seismic performance of the slender 800 kV composite BPS.